Assessing the Effectiveness of Top Leaf Meal of Indigofera zollingeriana to Substitute Soybean Meal through Evaluation on Protein Quality and Metabolic Energy in Poultry Feed - Rizki Palupi; Sumiati Sumiati; Dewi Apri Astuti; Luki Abdullah (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
This study aimed to evaluate protein quality of top leaf meal of Indigofera zollingerina based on its net protein utilization (NPU) as well as to evaluate its metabolizable energy. Fifty broiler chicks were used in determination of NPU while fifteen broiler strain Cobbs chickens aged 5 weeks were used for metabolizable energy measurement. This study used descriptive method in which data obtained were analyzed and compared to NPU and metabolizable energy of soybean meal. The results showed that top leaf meal of Indigoferazollingerinahad NPU of 38.58 – 46.98, which is 70.14% - 85-42% of that of soybean meal (55). Its metabolizable energy was 2791.12 kcal/kg and was 9.46% higher than that of soybean meal. As the NPU and metabolizable energy were close to those of soybean meal, top leaf meal of Indigoferazollingerinacan be used to substitute protein from soybean meal in poultry feed.